Ketamine-assisted psychotherapy treatment of chronic pain and comorbid depression: a pilot study of two approaches - Batievsky, Daniella; Weiner, Michelle; Kaplan, Shari B.; Thase, Michael Edward; Maglione, Domenick Nicholas; Vidot, Denise Christina (Frontiers in Pain Research, 2023)
Chronic pain and depression diagnoses are skyrocketing. There is an urgent need for more effective treatments. Ketamine was recently established to alleviate pain and depression, but many gaps remain in the scientific literature. This paper reports the findings of an observational preliminary study that explored the efficacy of ketamine-assisted psychotherapy (KAPT) for chronic pain/major depressive disorder (MDD) comorbidity. Researchers evaluated two KAPT approaches to determine optimal route of administration/dose. Ten individuals diagnosed with a chronic pain disorder and MDD receiving KAPT were recruited: five individuals pursuing the psychedelic approach (high doses administered intramuscularly 24 h before therapy) and five individuals pursuing the psycholytic approach (low doses administered sublingually via oral lozenges during therapy). To evaluate differences between altered states of consciousness each approach induces, participants completed the Mystical Experience Questionnaire (MEQ30) after their first (T-1), third (T-2) and sixth/final (T-3) treatment sessions. Primary outcomes were change in Beck Depression Inventory (BDI) scores and Brief Pain Inventory (BPI) Short Form scores from baseline (T0) to (T-1)–(T-3). Secondary outcomes were changes in Generalized Anxiety Disorder (GAD-7) Scale scores and Post-Traumatic Stress Disorder Checklist (PCL-5) scores at each timepoint. Statistically significant differences between each approach were not observed, but the small sample’s limited statistical power makes changes seen worth noting. All participants’ symptoms declined throughout treatment. Psychedelic treatment participants saw a larger, more consistent decrease. Researchers conclude that KAPT may be effective for treating chronic pain/MDD comorbidity, anxiety and Post-Traumatic Stress Disorder (PTSD). Findings imply that the psychedelic approach may be more effective. This pilot study serves as a basis for more extensive research that will inform how clinicians administer treatment to optimize outcomes.